2002
DOI: 10.1136/jcp.55.11.829
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the expression of p53, p21, Bax and the induction of apoptosis between patients with basal cell carcinoma and normal controls in response to ultraviolet irradiation

Abstract: Aim: Ultraviolet light (UV) is known to cause DNA damage in the epidermis. The damaged DNA is repaired or deleted by apoptosis to prevent the generation of cancer. It has been suggested that a deficient apoptotic mechanism may predispose individuals to skin cancer. Therefore, the response of normal controls and patients with basal cell carcinoma (BCC) to UV irradiation was investigated. Methods: The buttock skin from normal volunteers and patients with BCC was irradiated using solar simulated radiation (SSR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 53 publications
3
18
0
1
Order By: Relevance
“…Recent studies have suggested that p21 and promoters of apoptosis are coregulated by p53 to coordinate the damage response. 18,19 In H1299-pBIG-p21 cells overexpressing p21, we do not see a concomitant increase in apoptosis to balance the increase in p21-mediated prosurvival factors (data not shown). In addition, we were unable to detect increased radiation resistance in H1299 cells in the presence of overexpressed p21 protein, thereby suggesting that p21 may not offer protection against IR-induced cell death.…”
Section: Discussionmentioning
confidence: 54%
“…Recent studies have suggested that p21 and promoters of apoptosis are coregulated by p53 to coordinate the damage response. 18,19 In H1299-pBIG-p21 cells overexpressing p21, we do not see a concomitant increase in apoptosis to balance the increase in p21-mediated prosurvival factors (data not shown). In addition, we were unable to detect increased radiation resistance in H1299 cells in the presence of overexpressed p21 protein, thereby suggesting that p21 may not offer protection against IR-induced cell death.…”
Section: Discussionmentioning
confidence: 54%
“…Basal cell carcinoma (BCC) is considered to be the most common skin malignancy and its incidence is on the rise worldwide because of increased exposure to UV light and ozone depletion in various parts of the world due to environmental and industrial pollution [16]. Exposure to UV light results in DNA damage that leads to development of skin cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive apoptosis of alveolar type II (ATII) cells, augmented p53 expression due to DNA damage, and chronic lung inflammation have collectively been implicated in the development of diffuse alveolar damage (DAD) and idiopathic pulmonary fibrosis (IPF) (61) and have each been found to promote accelerated PF in various animal models (36,39,44). Increased expression of p53 by apoptotic ATII cells surrounding the fibrotic lesions in IPF patients implicates p53 in the development of IPF.…”
mentioning
confidence: 99%